QUESTION ANSWERING SYSTEM INFORMASI PARIWISATA KOTA PALEMBANG - Marga Lenni; R. Kristoforus Jawa Bendi (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2019)
The development of information technology is very rapid, resulting in an overflow of data. The amount of data can be used to obtain information needed by the user. The problem is, not all information can be found easily, especially very specific information. Likewise information about tourism. One way to overcome these problems is to utilize Natural Language Processing Technology, especially Question Answering System, which allows Computers to understand the meaning of Questions posed by users in natural languages. This study built a simple Question Answering System application. Application developed with PHP programming language, and MySql database. Preprocessing techniques used are Tokenization, Part-Of-Speech tagging, and Named Entity Recognation. The test result show that the application is able to provide answers to user questions of 82,05%.